2019
DOI: 10.1021/acs.jctc.9b00083
|View full text |Cite
|
Sign up to set email alerts
|

On Achieving High Accuracy in Quantum Chemical Calculations of 3d Transition Metal-Containing Systems: A Comparison of Auxiliary-Field Quantum Monte Carlo with Coupled Cluster, Density Functional Theory, and Experiment for Diatomic Molecules

Abstract: The bond dissociation energies of a set of 44 3d transition metal-containing diatomics are computed with phaseless auxiliary-field quantum Monte Carlo (ph-AFQMC) utilizing a correlated sampling technique. We investigate molecules with H, N, O, F, Cl, and S ligands, including those in the 3dMLBE20 database first compiled by Truhlar and co-workers with calculated and experimental values that have since been revised by various groups. In order to make a direct comparison of the accuracy of our ph-AFQMC calculatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
121
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 78 publications
10
121
0
Order By: Relevance
“…This approach performs most efficiently when the ligand being removed is small, as indicated by our previous work in which the reduction in statistical error vs the uncorrelated approach was several times larger for MnH than for MnCl. 40 Similar behavior is found for the transition metal complex systems studied here, as shown in Fig. 2 for [Cu(H 2 ) 4 ] + .…”
Section: Computational Detailssupporting
confidence: 83%
See 1 more Smart Citation
“…This approach performs most efficiently when the ligand being removed is small, as indicated by our previous work in which the reduction in statistical error vs the uncorrelated approach was several times larger for MnH than for MnCl. 40 Similar behavior is found for the transition metal complex systems studied here, as shown in Fig. 2 for [Cu(H 2 ) 4 ] + .…”
Section: Computational Detailssupporting
confidence: 83%
“…[31][32][33][34][35] However, the reliability of CC methods for transition metal systems, even when multireference effects are approximated, has been the subject of vigorous debate, as illustrated by recent studies on transition metal diatomic-ligand systems. 24,[36][37][38][39][40][41] de Oliveira-Filho and co-workers found that even multireference CCSD(T) could not predict the bond dissociation energies (BDEs) for some diatomics accurately with respect to experimental measurements. A recent study by Head-Gordon and co-workers found that high levels of CC, up to CCSDTQ, are required for chemical accuracy against an exact method known as Adaptive Sampling Configuration Interaction (ASCI) results, albeit in a small basis set.…”
Section: Introductionmentioning
confidence: 99%
“…For ionization and bonddissociation energies of transition metal atoms and diatomics, respectively, this yielded very high accuracy while reducing the computational cost compared to double-precision calculations. 61,62 For pentacene, the largest molecule considered in this work, we verified with separate calculations in the STO-3G basis that single-and double-precision calculations gave statistically indistinguishable results.…”
Section: Computational Detailssupporting
confidence: 54%
“…AFQMC has been successfully applied in recent years to a number of challenging problems in both quantum chemistry [29][30][31][32][33] and solid state physics [34][35][36] . However, the broad applicability of the method is not as well under-stood as more traditional quantum chemistry approaches which have seen decades worth of sustained development and benchmarking.…”
Section: Introductionmentioning
confidence: 99%
“…Often short determinantal expansions from complete active space self-consistent field (CASSCF) wavefunctions 31,33 or non-orthogonal multi-Slater deteraminant trial wavefunction 32 can help to restore the accuracy of the method. However, since multideterminant wavefunctions scale exponentially with system size, this approach to improving the trial wavefunction is ultimately limited, particularly for large scale applications.…”
Section: Introductionmentioning
confidence: 99%